Multifactorial Control of Iteration Events in a Modular Polyketide Assembly Line1. Issue 20 (18th April 2013) - Busch, Benjamin; Ueberschaar, Nico; Behnken, Swantje; Sugimoto, Yuki; Werneburg, Martina; Traitcheva, Nelly; He, Jing; Hertweck, Christian
<x xml:space="preserve">Abstract</x> Freedom and control: First insights into the rare programmed iteration of an individual polyketide synthase (PKS) module were obtained from the analysis and mutation of aureothin (1) synthase. The first ketosynthase (KS) domain primes the PKS, allowing intermediate retrotransfer. Addition of a designated loading module results in a complete loss of iteration. The downstream KS functions as a gatekeeper for correct chain length.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>